The Intergenerational Transfer of Welfare Dependency: Some Statistical Evidence - Antel, John J. (The Review of Economics and Statistics, 1992)
Does a mother's welfare receipt increase the future dependency of her children? Does the welfare system, thus, stimulate the dependency of future generations? Parameter estimates reported here suggest such intergenerational effects. The sample comprises young girls and their mothers. After control for observed and unobserved heterogeneity, a mother's welfare participation is found to increase her daughter's later welfare dependency. Copyright 1992 by MIT Press.